ANALISIS WACANA KRITIS NORMAN FAIRCLOUGH TERHADAP PEMBERITAAN DUGAAN SERANGAN SIBER BANK SYARIAH INDONESIA DI MEDIA BBC - Musdalifah Musdalifah (JIKE: Jurnal Ilmu Komunikasi Efek, 2025)
This study aims to analyze the news of the alleged cyber attack of Bank Syariah Indonesia in the BBC media using Norman Fairclough's Critical Discourse Analysis. The problems focused on 1) framing BBC news, 2) framing the ideology of BBC news, 3) religious dimension in framing news. The type of research used is qualitative with secondary data sources, namely news texts posted by the BBC entitled "BSI Allegedly Hit by a Cyber Attack, Observers Call Bank Defense System 'Not Strong'" The first analysis flow carried out is simaah and then data analysis based on critical discourse analysis (AWK), data reduction, data display, and conclusion drawn. The results of the study found that 1) framing the news of the Bank Syariah Indonesia cyberattack in the BBC news report directs readers to look at the incident objectively by placing BSI as a victim who must receive attention from both the government and the public. 2) The BBC's ideological framing in this news emphasizes the importance of strengthening Indonesia's banking digital defense system through professional crisis management, and mitigation efforts carried out by BSI.  3) The religious dimension is influenced in the Language and Framing used by the BBC when giving the case of the alleged BSI cyberattack. Sharia compliance that is not carried out as it should, namely maintaining and protecting customer data as consumers from data leakage by a wide range of malicious parties. Further research suggestions can be made by comparing the results of two expert views from the analysis of critical discourse on news using the views of Michel Foucault, Teun A. Van Dijk, Roger Fowler, Ruth Wodak, Theo Van Leeuwen, Sara Mills Keywords:. Cyberattacks, Critical discourse analysis, Banking institutions